Simulating biome distribution on the Tibetan Plateau using a modified global vegetation model - Ni, Jian; Herzschuh, Ulrike (Prof. Dr.) (Arctic, Antarctic, and Alpine Research, 2011)
We used a regionally modified global vegetation model (BIOME4-Tibet) to simulate biome distribution on the Tibetan Plateau under current climate conditions derived from regional meteorological observations. The bioclimatic limits (mean temperatures of the coldest and warmest months, minimum temperature, growing degree-days on 5 degrees C and 0 degrees C bases) for some key alpine plant functional types (temperate deciduous and conifer trees, boreal deciduous and conifer trees, desert woody plants, tundra shrubs, cold herbaceous plants, and lichens/forbs) were redefined based on regional vegetation-climate relationships. Modern vegetation maps confirmed that the BIOME4-Tibet model does a better job of simulating biome patterns on the plateau (gridcell agreement 52%) than the original BIOME4 model (35%). This improved model enhanced our ability to simulate temperate conifer forest, cool conifer and mixed forest, evergreen taiga, temperate xerophytic shrubland, temperate grassland and desert, and steppe and shrub tundra biomes, but made a negligible or reduced difference to the prediction of temperate deciduous forest, warm-temperate mixed forest, and three tundra biomes (erect dwarf-shrub tundra, prostrate dwarf-shrub tundra, and cushion forb, lichen, and moss tundra). Future modification of the vegetation model, by increasing the number of shrub and herb plant functional types, re-parameterization of more precise bioclimatic constraints, and improved representation of soil, permafrost, and snow processes, will be needed to better characterize the distribution of alpine vegetation on the Tibetan Plateau.